Implementation of Human Resource Transformation in Adapting to the Digital Information System at Kantor Imigrasi Kelas I Tpi Malang - Mansyur, Muhammad Nur; Supriyatno, Budi; Hakim, Azis (Dinasti International Journal of Digital Business Management, 2025)
Digital transformation in public services refers to changing the way governments serve citizens through the use of technology, making processes faster, easier, and more transparent. Integrating data and processes across various agencies not only enhances efficiency but also strengthens accountability and public trust in government services. The traditional bureaucratic model often faces obstacles such as lengthy procedures, excessive document collection, and manual interventions that lead to non-transparency and opportunities for corruption. Public service is considered a crucial element for society in accordance with Law No. 25 of 2009. Its purpose is to support the fulfillment of diverse public needs and to emphasize the necessity for government institutions to operate optimally. The quality of governance can be measured by its ability to safeguard democracy, protect human rights, improve the public’s economic welfare, and wisely protect and manage the nation’s resources. Efforts to improve the quality of public services are crucial to strengthening public trust in the government. There is a significant need to enhance public services, as reflected by the low level of public satisfaction. Many complaints concern complex procedures, slow processes, high costs, and the unprofessional attitudes of officers that fail to reflect excellent service. Over time, however, public services have become increasingly important in streamlining bureaucratic systems. This study aims to determine how the implementation of employee human resource transformation responds to the digital information system at the Class I Immigration Office TPI Malang. The research uses a qualitative method, with data and information collected through interviews, observations, and literature or document studies. Informants in this study were selected using the snowball sampling technique. The digital skills of employees at the Class I Immigration Office TPI Malang are already good. These digital skills significantly increase productivity and efficiency through process automation, allowing employees to focus on higher-value tasks. There remains a need to improve digital literacy skills. Employee training and development at the Class I Immigration Office TPI Malang are well-implemented. Applying digital training effectively ensures that human resources are better prepared to face the challenges of digital information system transformation, adapt quickly to changes, and contribute significantly to achieving strategic goals. The implementation of digital services at the Class I Immigration Office TPI Malang is also good. Digital infrastructure is already evenly distributed but still needs improvement, along with human resources who are technologically competent.